Vv. Aa. Poesía Buenos Aires; Vv.Aa. La Rosa Blindada. Buenos Aires: Ediciones de la Biblioteca Nacional, 2014 - Catalano, María Agustina (2015)
Fil: Fil: Catalano, María Agustina. Universidad Nacional de Mar del Plata; Argentina.